2017
DOI: 10.1038/ncomms14749
|View full text |Cite
|
Sign up to set email alerts
|

RNA surveillance via nonsense-mediated mRNA decay is crucial for longevity in daf-2/insulin/IGF-1 mutant C. elegans

Abstract: Long-lived organisms often feature more stringent protein and DNA quality control. However, whether RNA quality control mechanisms, such as nonsense-mediated mRNA decay (NMD), which degrades both abnormal as well as some normal transcripts, have a role in organismal aging remains unexplored. Here we show that NMD mediates longevity in C. elegans strains with mutations in daf-2/insulin/insulin-like growth factor 1 receptor. We find that daf-2 mutants display enhanced NMD activity and reduced levels of potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 51 publications
1
69
0
Order By: Relevance
“…This would have important consequences for the removal of aberrant mRNAs and could contribute to the decline of nonsense-mediated decay observed with age. 38 Significantly the function of other membrane-less structures such as the nucleolus are likely to be negatively affected by the aggregation of RBPs with LC prion-like domains. For instance, we identified that the nucleolus RBP Fibrillarin (FIB-1) was highly prone to aggregate with age.…”
Section: Discussionmentioning
confidence: 99%
“…This would have important consequences for the removal of aberrant mRNAs and could contribute to the decline of nonsense-mediated decay observed with age. 38 Significantly the function of other membrane-less structures such as the nucleolus are likely to be negatively affected by the aggregation of RBPs with LC prion-like domains. For instance, we identified that the nucleolus RBP Fibrillarin (FIB-1) was highly prone to aggregate with age.…”
Section: Discussionmentioning
confidence: 99%
“…Lifespan assays. Lifespan assays were conducted as previously described (Son et al, 2017). Young (day 0) adult worms that were grown on control RNAi and daf-2…”
Section: Rnai Inductionmentioning
confidence: 99%
“…RNA extraction and quantitative RT-PCR. RNA extraction and qRT-PCR were performed as previously described with minor modifications (Son et al, 2017). When worms that were fed with OP50 or RNAi bacteria reached L4 or young adult stage (day 0), 50 ÎŒM FUdR was supplemented.…”
mentioning
confidence: 99%
“…In C. elegans, NMD is governed by the activity of several genes, including smg-1/2/3/4/5/6/7, which are responsible for the detection of aberrant transcripts, releasing the stalled ribosome, and degrading the transcript (Hug et al, 2016). Given that the translation of NMD prone transcripts appeared to be regulated by DR and that NMD has been shown to play a role in ILS mediated longevity (Son et al, 2017), we hypothesized that NMD plays a role in DR induced longevity. We tested the importance of NMD in longevity using mutants defective in smg-1/2/3/4/5/6/7 subject to AL or DR starting at adulthood.…”
Section: Nmd Genes Smg-6 and Smg-7 Are Required For Dr-mediated Lifesmentioning
confidence: 99%
“…The gene F13G3.6 was investigated as it was reported to have a PTC bearing isoform whose expression is dependent on the activity of the NMD gene smg-2 in C. elegans (Son et al, 2017). This gene is similar to human B3GNTL1, which plays a role in elongating N-glycans on mucin proteins.…”
Section: Intron Retention Increases Under Drmentioning
confidence: 99%